Photopatternable materials for guided cell adhesion and growth. (5th January 2022) - Kourti, Dimitra; Kanioura, Anastasia; Chatzichristidi, Margarita; Beltsios, Konstantinos G.; Kakabakos, Sotirios E.; Petrou, Panagiota S.
Graphical abstract: Abstract: Cells in vivo are grown in a highly organized environment defined by the interactions with other cells and the extracellular matrix proteins. Thus, in order to shed light in cellular functions such as adhesion, migration, proliferation, apoptosis and differentiation, the creation of cell culture surfaces that mimic the in vivo environment has emerged. To create such surfaces, many microfabrication techniques have been applied so far. In this review, we focus on application of light-assisted patterning techniques for construction of either 2D or 3D cell culture substrates. In the first section of the review, the principle of the main light-assisted patterning approaches is presented and their advantages and limitations are discussed. In the second section, the influence of micro/nanopatterned surfaces fabricated with the described methods, on vital cell functions is presented, along with the significance of these findings in the field of tissue engineering and regenerative medicine.